2022
DOI: 10.1371/journal.pmed.1003903
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between congenital heart disease and cancer in Swedish children: A population-based cohort study

Abstract: Background Birth defects have been consistently associated with elevated childhood cancer risks; however, the relationship between congenital heart disease (CHD) and childhood cancer remains conflicting. Considering the increasing patient population with CHD after improvements in their life expectancies, insights into this relationship are particularly compelling. Thus, we aimed to determine the relationship between CHD and cancer in Swedish children. Methods and findings All individuals registered in the Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Subtype missing 3 (0.6) 1 (4.5) 0 (0.0) 2 (0.5) study of CHDs, after adjustment for Down syndrome, CHD was associated with increased risk of lymphoma (HR: 1.6; 95% CI: 1.1-2.4; n = 1,273). In this cohort, an elevated risk of lymphoma (HR = 8.13, 95% CI: 4.06-16.30) was also observed in children with complex CHD, 58 as previously reported. 59,60 While this was not observed in our study, it could be due to the limited number of cases (n = 4) and controls (n = 7)…”
Section: Characteristicsupporting
confidence: 89%
“…Subtype missing 3 (0.6) 1 (4.5) 0 (0.0) 2 (0.5) study of CHDs, after adjustment for Down syndrome, CHD was associated with increased risk of lymphoma (HR: 1.6; 95% CI: 1.1-2.4; n = 1,273). In this cohort, an elevated risk of lymphoma (HR = 8.13, 95% CI: 4.06-16.30) was also observed in children with complex CHD, 58 as previously reported. 59,60 While this was not observed in our study, it could be due to the limited number of cases (n = 4) and controls (n = 7)…”
Section: Characteristicsupporting
confidence: 89%
“…In this study, we analyzed the impact of the cardiac defect on T-cell development in patients with CHD, a population known to be at increased risk for infections, cancer, and autoimmune diseases [ 16 , 46 49 ]. Previous research has mainly linked the compromised T-cell compartment observed in these patients with early-life thymectomy [ 50 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large population-based cohort study by Kampitsi et al [ 10 ] reported a 64% increased risk of lymphoma and more than 300% of hepatoblastoma, respectively. The risk of lymphoma was particularly elevated in children with complex CHD and that of leukemia in patients with Down syndrome [ 10 ]. Additionally, a recent Swedish register-based study confirmed the increased cancer risk in patients with CHD [ 15 ].…”
Section: Cancer Risk In Chd Patientsmentioning
confidence: 99%
“…Children with congenital defects have a significantly higher risk of developing some type of cancer, including leukemia, tumors of the central nervous system, tumors of the sympathetic nervous system, and soft tissue sarcomas [ 3 , 4 , 5 , 6 , 7 , 8 ]. Cancer risk is especially increased in CHD children with complex defects [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%